How dependent Is Germany on raw material imports? An analysis of inputs to produce key technologies - Lisandra Flach; Isabella Gourevich; Leif Grandum; Lisa Scheckenhofer; Feodora Teti (CESifo GmbH, 2022)
The production of key technologies such as electric motors, batteries and wind turbines is often dependent on imported raw materials. Using German data, we analyze important raw materials that are re-quired to produce key technologies in Germany. We identify nine critical raw materials (1) with a high degree of supplier concentration and (2) which are used in the production of more than four key technologies. Except rare earths, Germany imports all critical raw materials from at least four of the top 5 exporters worldwide, which indicates a high diver-sification of sourcing. However, it is crucial to deepen existing trade rela-tionships and to acquire new sourcing partners to increase resilience. China is among the top 5 exporters worldwide in seven out of the nine listed critical raw materials. We evaluate working conditions, environment, and democracy in the sourcing countries. Germany's sourcing countries score better than those of the US and China. However, raw materials such as boron or rare earths are often imported from countries that perform poorly in those categories.
Keywords: 330